FGF8 morphogen gradients are differentially regulated by heparan sulphotransferases Hs2st and Hs6st1 in the developing brain - Wai-Kit Chan (Biology Open, 2017)
Fibroblast growth factor (FGF) morphogen signalling through the evolutionarily ancient extracellular signalling-regulated kinase/mitogen activated protein kinase (ERK/MAPK) pathway recurs in many neural and non-neural developmental contexts, and understanding the mechanisms that regulate FGF/ERK function are correspondingly important. The glycosaminoglycan heparan sulphate (HS) binds to FGFs and exists in an enormous number of differentially sulphated forms produced by the action of HS modifying enzymes, and so has the potential to present an extremely large amount of information in FGF/ERK signalling. Although there have been many studies demonstrating that HS is an important regulator of FGF function, experimental evidence on the role of the different HS modifying enzymes on FGF gradient formation has been lacking until now. We challenged ex vivo developing mouse neural tissue, in which HS had either been enzymatically removed by heparanase treatment or lacking either the HS modifying enzymes Hs2st (Hs2st−/− tissue) or Hs6st1 (Hs6st1−/− tissue), with exogenous Fgf8 to gain insight on how HS and the function of these two HS modifying enzymes impacts on Fgf8 gradient formation from an exogenously supplied source of Fgf8 protein. We discover that two different HS modifying enzymes, Hs2st and Hs6st1, indeed differentially modulate the properties of emerging Fgf8 protein concentration gradients and the Erk signalling output in response to Fgf8 in living tissue in ex vivo cultures. Both Hs2st and Hs6st1 are required for stable Fgf8 gradients to form as rapidly as they do in wild-type tissue while only Hs6st1 has a significant effect on suppressing the levels of Fgf8 protein in the gradient compared to wild type. Next we show that Hs2st and Hs6st1 act to antagonise and agonise the Erk signalling in response to Fgf8 protein, respectively, in ex vivo cultures of living tissue. Examination of endogenous Fgf8 protein and Erk signalling outputs in Hs2st−/− and Hs6st1−/− embryos suggests that our ex vivo findings have physiological relevance in vivo. Our discovery identifies a new class of mechanism to tune Fgf8 function by regulated expression of Hs2st and Hs6st1 that is likely to have broader application to the >200 other signalling proteins that interact with HS and their function in neural development and disease.